On the role of the electric dipole moment in the diffraction of biomolecules at nanomechanical gratings. Issue 6 (12th September 2016) - Knobloch, Christian; Stickler, Benjamin A.; Brand, Christian; Sclafani, Michele; Lilach, Yigal; Juffmann, Thomas; Cheshnovsky, Ori; Hornberger, Klaus; Arndt, Markus
Abstract : We investigate effects of a permanent electric dipole moment on matter‐wave diffraction at nanomechanical gratings. Specifically, the diffraction patterns of hypericin at ultra‐thin carbonaceous diffraction masks are compared with those of a polar and a non‐polar porphyrin derivative of similar mass and de Broglie wavelength. We present a theoretical analysis of the diffraction of a rotating dipole highlighting that small local electric charges in the material mask can strongly reduce the interference visibility. We discuss the relevance of this finding for single grating diffraction and multi‐grating interferometry with biomolecules.